Inspiration Class for children of Indonesian Migrant Workers in Kuala Lumpur - Muhammad Randi Setiadi; Siti Nur Azizah; Ariel Alvi Zahry; Shaffitri Kurnia Putri; Zuhaimi Santari Hayus; Wiwit Saputri; Siti Julaeha (Journal of Society, Community and Business Development, 2023)
Children are the nation's next generation who play an important role in the development of a nation. However, not all children have access to adequate education, including children who are descendants of migrants in Malaysia. In order to realize educational equality, PKM is holding inspirational class activities through professional introductions delivered directly by education practitioners for children of PMI descent in Kuala Lumpur, Malaysia. This activity was welcomed by the Head of SIKL and SB managers as well as all the children of PMI descent who live there. Through PKM, children become more motivated to learn and have high aspirations. This self-confidence is a good first step for them to be more enthusiastic and brave to have high ideals. The result of this activity is that children not only have motivation to learn and have high aspirations, but it also gives them an understanding that learning is fun and has a positive impact on their future.